An unusual long standing metallic foreign body in nasopharynx in an adult - K., Freni J.; Jo, Jibu K.; Sankar, Prasanth (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
This case report was to highlight the occurrence of a long standing unusual foreign body in the nasopharynx in an adult. Foreign bodies are common in ENT practice universally. At times they may present as emergency requiring urgent intervention and many a times they go unnoticed as these are not suspected. Nasopharyngeal foreign bodies are rare in any age group. A 70 year old man presented to neurology department with complaints of headache of 1 month duration. CT brain angiography showed atherosclerotic wall calcifications in bilateral cavernous segment of ICA and there was an incidental detection of a metallic foreign body in the posterior wall of oropharynx. History revealed accidental ingestion of a ring into mouth at 1 year of age. Diagnostic nasal endoscopy (DNE) was done, FB (foreign  body) ring was seen at the level of left torus tubarius in nasopharynx and same removed in to intraorally. Care should be taken while removing these FBs. Digital manipulation for removal of such FBs are hazardous and should be avoided at all cost.